Pengaruh Net Profit Margin, Debt To Equity Ratio Dan Current Ratio Terhadap Dividen Payout Ratio Melalui Return On Asset - Melva Saidah Tanjung; Liza Novietta; Desi Ika (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
The results showed that the Net Profit Margin had a significant effect on Return On Assets, the Debt to Equity Ratio had a significant effect on Return On Assets, the Current Ratio had a significant effect on Return On Assets, the Net Profit Margin had no significant effect on the Dividend Payout Ratio, and the Debt to Equity Ratio had a significant effect on significant effect on the Dividend Payout Ratio, the Current Ratio has no significant effect on the Dividend Payout Ratio, Return On Assets has a significant effect on the Dividend Payout Ratio, Net Profit Margin has a significant effect on the Dividend Payout Ratio through Return On Assets, Debt to Equity Ratio has a significant effect on the Dividend Payout Ratio through Return On Assets and Current Ratio has no significant effect on Dividend Payout Ratio through Return On Assets.